Intersectional cosmopolitanism: Muslim women's engagement with polygamy on Malaysian and Indonesian screens. Issue 2 (3rd April 2019) - Zainal, Humairah
ABSTRACT: This article interrogates how the diverse realities of Muslim women fray the concept of 'Muslim cosmopolitanism' in Southeast Asia. By comparing how Malaysian Muslim women interpret polygamy in Malaysian and Indonesian screens, this article problematises the idea of a unified cosmopolitanism experienced by Muslims from the Malay world. Based on findings from interviews with 25 educated women, this article shows that media representations of polygamy and Muslim femininity can differ even between two Southeast Asian countries sharing common gendered and religious practices. It argues that the women's understanding of polygamy is based on the intertwinement of their ethnic, gendered and classed subjectivities that are not necessarily informed by their religious beliefs per se but rather by the broader socio-political contexts in which they live. Through this embodiment of intersectional cosmopolitanism, they not only disrupt existing notions of 'Muslim cosmopolitanism' but highlight the heterogeneous experiences of Muslims within Southeast Asia.